Aspartic acid racemization method for age estimation in human tissues: a review - Gumpangseth T; Pasuk Mahakkanukrauh (Pusat Perubatan Universiti Kebangsaan Malaysia, 2017)
The amino acid racemization is a chemical reaction process that depends on the property change of proteins in the organism. There is change in the concentration of L-and D-amino acids in during life and after death, as well. This change leads to the relationship with aging process. Aspartic acid (Asp) is non-essential amino acid which is commonly utilized on racemization because it has most rapidly accumulated of D-aspartic acids of all amino acids. Therefore, aging is related to the interconversion of amino acids, which is a useful tool for age estimation in forensic science. Aspartic acid racemization can occur in many human structures e.g. teeth, bone, articular cartilage, intervertebral disc, yellow ligament, skin, lung parenchyma, aorta, and eye-lens. Additionally, the relationship between aspartic acid racemization and age can be used for investigation of protein turnover and pathological diseases. There are different aspartic acid preparation methods which obtain different results. In this review, we describe aspartic acid racemization method, several factors of racemization, application of racemization for age estimation including several preparation methods based on racemization in both teeth and bones.